Determining the likelihood that fatigue was present in a road accident: A theoretical review and suggested accident taxonomy. (December 2018) - Dawson, Drew; Reynolds, Amy C.; Van Dongen, Hans P.A.; Thomas, Matthew J.W.
Summary: Estimates in developed countries of the extent to which fatigue contributes to road accidents range from as low as 5% to as high as 50% of all accidents. Compared with other causes of road accidents (e.g., speeding, drink-driving), the variability in these estimates is exceptionally high and may be indicative of the difficulty in determining the likelihood of fatigue as a cause of road accidents. This review compares differences in the way road accidents are classified as fatigue-related (or not) by expert panels and road safety regulators, highlighting conflicting conceptual approaches, lack of consistency, and the poor psychometric qualities of classification rules used across jurisdictions. In order to facilitate future research, the review then proposes a new theoretical approach and a potentially more logical accident 'taxonomy'. A putative accident 'taxonomy' is proposed using two dimensions: (1) estimating the likelihood that a driver was fatigued at the time of the accident, and (2) estimating the degree to which accident phenomenology is consistent with fatigue-related error. This 'taxonomy' could assist accident investigators and road safety regulators to more reliably quantify the contribution of fatigue to road accidents, and may also assist researchers and regulators in the post-hoc interrogation of existing accident databases to better determine the relative incidence of fatigue-related road accidents.